MENINGKATKAN KEMAMPUAN MENELAAH ISI, STRUKTUR, DAN KAIDAH KEBAHASAAN TEKS EKSPLANASI DENGAN MENERAPKAN METODE INKUIRI SISWA KELAS VIII B SEKOLAH MENENGAH PERTAMA NEGERI 3 TABANAN - Ni Made Sueni; Subaker I Wayan; Sandeni Ni Luh Made (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2022)
One of the 14 texts taught at the junior high school level is explanatory text, explanatory text is an interesting text to study. The purpose of this study is to contribute thoughts/opinions in order to improve the ability to examine the content, structure, and linguistic rules of explanatory texts for class VIII B students of Tabanan 3 Junior High School in the 2021/2022 academic year. This research is a classroom action research which consists of two cycles with a total of 30 students. The data collection method used is the observation method and the test method. The observation method was used to obtain data about students' attitudes and behavior, the test method was used to determine the student's ability to examine the content, structure, and linguistic rules of explanatory texts. The results showed that the ability to examine the content, structure, and linguistic rules of the explanatory text of class VIII B State Junior High School 3 Tabanan in the 2021/2022 academic year after applying the inquiry method had increased. This is evident from the average value in the pre-cycle of 65.00, the first cycle the average value of 70.67. In the second cycle the average value obtained was 85.00. The increase from pre-cycle to cycle I was 8.72%. The increase from cycle I to cycle II was 20.28%. The increase in the score is a sign that the ability to examine the content, structure, and linguistic rules of the explanatory text of class VIII B State Junior High School 3 Tabanan for the academic year 2021/2022 is getting better after applying the inquiry method. Thus, it is recommended for Indonesian language teachers to apply the inquiry method in learning activities because it has been proven that the application of the inquiry method can improve students' abilities.